Method for producing positive electrode active material

JP7652504B2Active Publication Date: 2025-03-27LG CHEM LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2022088802
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2017-11-24
Filing Date
2022-05-31
Publication Date
2025-03-27
Estimated Expiration
2038-11-23

Smart Images

  • Figure 0007652504000001
    Figure 0007652504000001
  • Figure 0007652504000002
    Figure 0007652504000002
Patent Text Reader

Abstract

A method for producing a positive electrode active material is provided. [Solution] The present invention relates to a method for manufacturing a positive electrode active material, the method comprising the steps of: charging a reaction mixture containing a lithium source material and a nickel-manganese-cobalt precursor into a first crucible, and subjecting the reaction mixture to a first heat treatment at a temperature of 500°C to 800°C to form a calcination mixture; removing the calcination mixture from the first crucible and crushing or classifying it; and charging the crushed or classified calcination mixture into a second crucible, and subjecting the crushed or classified calcination mixture to a second heat treatment at a temperature of 700°C to 1000°C in an atmosphere with an oxygen partial pressure of 20% or less to form a lithium-nickel-manganese-cobalt-based positive electrode active material, wherein the volume of the calcination mixture formed after the first heat treatment is 20% to 50% of the volume of the reaction mixture charged into the first crucible.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] [Cross - reference to Related Applications] This application claims the benefit of priority based on Korean Patent Application No. 10 - 2017 - 0158817, filed on November 24, 2017, and all of the contents disclosed in the document of the Korean patent application are incorporated herein by reference in their entirety.

[0002] The present invention relates to a method for manufacturing a positive electrode active material, and more particularly, to a method for manufacturing a lithium nickel manganese cobalt oxide - based positive electrode active material having excellent productivity, quality uniformity, and physical properties.

Background Art

[0003] With the development of technologies and the increasing demand for mobile devices, the demand for secondary batteries as an energy source has been rapidly increasing. Among such secondary batteries, lithium secondary batteries having high energy density, high voltage, long cycle life, and low self - discharge rate have been widely used and are commonly used.

[0004] As positive electrode active materials for lithium secondary batteries, various lithium transition metal oxides such as LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiFePO4, Li(Ni a Co b Mn c )O2 (where a, b, and c are independently atomic fractions of oxide - forming elements, 0 < a < 1, 0 < b < 1, 0 < c < 1, and a + b + c = 1) have been developed. Among these, Li(Ni a Co b Mn c )O2 has the advantage of being used for high capacity and high voltage and has been actively studied recently.

[0005] Conventional lithium nickel manganese cobalt - based oxides have been manufactured through a method in which a precursor such as nickel - manganese - cobalt hydroxide and a lithium raw material such as lithium hydroxide or lithium carbonate are mixed and then charged into a crucible and fired at a high temperature of about 750 to 950 °C.

[0006] However, in this conventional method, as the nickel-manganese-cobalt precursor and lithium raw material are mixed together, the volume increases, which reduces the amount of raw material that can be put into the crucible, resulting in a problem of reduced productivity. If the amount of finely divided raw material put into the crucible is increased to increase productivity, the firing is not performed uniformly, resulting in significant deviation in the quality of the positive electrode active material formed within the same crucible after firing. In addition, there is a problem in that unnecessary gases such as CO2 are generated during the firing process, which has a negative effect on the quality of the positive electrode active material.

[0007] Furthermore, in order to improve the capacity characteristics, high-concentration nickel-lithium nickel-manganese-cobalt-based positive electrode active materials with nickel content of 60 mol % or more have been developed recently. In the case of such high-concentration lithium nickel-manganese-cobalt-based positive electrode active materials, +2 From Ni +3 In general, firing is performed in an oxygen atmosphere in which an excessive amount of oxygen is introduced to oxidize the material. However, when firing is performed in an oxygen atmosphere, there are problems in that the temperature deviation in the firing furnace can be significant and the partial pressure of oxygen must penetrate to the inside of the material to be fired, which requires a long firing time. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Korean Patent Publication No. 2005-0083869 Summary of the Invention [Problem to be solved by the invention]

[0009] The present invention is intended to solve the above problems, and aims to provide a method for producing a positive electrode active material, which can provide a lithium nickel manganese cobalt-based positive electrode active material having uniform and excellent quality by producing the positive electrode active material through two-stage firing with different heat treatment temperatures and atmospheres.

[0010] Furthermore, the present invention aims to provide a method for producing a lithium nickel manganese cobalt-based positive electrode active material, which can provide a larger amount of positive electrode active material than conventional methods based on the same volume of crucible, and has excellent productivity. [Means for solving the problem]

[0011] The present invention provides a method for manufacturing a positive electrode active material, the method including: charging a reaction mixture containing a lithium source material and a nickel-manganese-cobalt precursor into a first crucible, and performing a first heat treatment at a temperature of 500°C to 800°C to form a pre-calcination mixture; removing the pre-calcination mixture from the first crucible and crushing or classifying it; and charging the crushed or classified pre-calcination mixture into a second crucible, and performing a second heat treatment at a temperature of 700°C to 1000°C in an atmosphere having an oxygen partial pressure of 20% or less to form a lithium-nickel-manganese-cobalt-based positive electrode active material, wherein a volume of the pre-calcination mixture formed after the first heat treatment is 20% to 50% of the volume of the reaction mixture charged into the first crucible. Effect of the Invention

[0012] According to the manufacturing method of the present invention, a lithium nickel manganese cobalt-based positive electrode active material having a large crystal size and little cation mixing and excellent physical properties and electrochemical characteristics can be obtained by performing two-step heat treatment with different heat treatment temperatures and atmospheres.

[0013] Furthermore, in the manufacturing method of the present invention, a pre-sintered mixture having a reduced volume compared to the reaction mixture is formed by performing a first heat treatment on the reaction mixture at a temperature of 500°C to 800°C, so a relatively large amount of the pre-sintered mixture can be placed in a crucible for the second heat treatment, resulting in excellent productivity. Specifically, the manufacturing method of the present invention can obtain a production volume 2 to 6 times higher with a crucible of the same volume compared to the existing method using a single sintering.

[0014] In addition, according to the manufacturing method of the present invention, unnecessary gases such as CO2 and moisture are released during the first heat treatment, and the second heat treatment is performed in a state where such by-products are removed, so that a positive electrode active material of excellent quality can be obtained even if the calcination is performed at a low oxygen partial pressure.

[0015] Furthermore, according to the manufacturing method of the present invention, it is possible to effectively eliminate variations in the quality of the positive electrode active material due to the placement position within the crucible. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The present invention will now be described in more detail.

[0017] The present inventors have conducted extensive research to produce a lithium nickel cobalt manganese-based positive electrode active material having high productivity, uniformity, and excellent quality. As a result, they have found that the above-mentioned object can be achieved by carrying out a first heat treatment under conditions of relatively low temperature and abundant oxygen to produce a pre-calcination mixture, pulverizing or classifying the mixture, and carrying out a second heat treatment under conditions of relatively high temperature and low oxygen, thereby completing the present invention.

[0018] Specifically, the method for preparing a positive electrode active material according to the present invention includes the steps of (1) putting a reaction mixture containing a lithium source material and a nickel-manganese-cobalt precursor into a first crucible and performing a first heat treatment at a temperature of 500°C to 800°C to form a pre-calcination mixture, (2) removing the pre-calcination mixture from the first crucible and pulverizing or classifying it, and (3) putting the pulverized pre-calcination mixture into a second crucible and performing a second heat treatment at a temperature of 700°C to 1000°C in an atmosphere with an oxygen partial pressure of 20% or less to form a lithium nickel manganese cobalt-based positive electrode active material. At this time, the volume of the pre-calcination mixture formed after the first heat treatment is about 20% to 50% of the volume of the reaction mixture put into the first crucible.

[0019] Hereinafter, each step of the manufacturing method according to the present invention will be described in more detail.

[0020] (1) Pre-firing mixture formation stage First, a reaction mixture containing a lithium source material and a nickel-manganese-cobalt precursor is placed in a first crucible.

[0021] As the lithium source material, various lithium source materials known in the art may be used without limitation, for example, lithium-containing carbonates (e.g., lithium carbonate, etc.), lithium-containing hydrates (e.g., lithium hydroxide I hydrate (LiOH·H2O), etc.), lithium-containing hydroxides (e.g., lithium hydroxide, etc.), lithium-containing nitrates (e.g., lithium nitrate (LiNO3), etc.), lithium-containing chlorides (e.g., lithium chloride (LiCl), etc.), etc. Preferably, the lithium source material may be at least one selected from the group consisting of lithium hydroxide and lithium carbonate.

[0022] As the nickel-manganese-cobalt precursor, various nickel manganese cobalt precursor materials known in the art may be used without limitation, for example, at least one selected from the group consisting of nickel manganese cobalt hydroxide, nickel manganese cobalt oxyhydroxide, nickel manganese cobalt carbonate, and nickel manganese cobalt organic complex may be used.

[0023] The nickel-manganese-cobalt precursor may be purchased commercially or may be prepared by methods well known in the art for preparing nickel-manganese-cobalt transition metal precursors.

[0024] For example, the nickel-manganese-cobalt transition metal precursor may be prepared by adding an ammonium cation-containing complexing agent and a basic compound to a metal solution containing a nickel-containing source material, a cobalt-containing source material, and a manganese-containing source material, and coprecipitation reaction.

[0025] The nickel-containing raw material may be, for example, nickel-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, or oxyhydroxide, etc., specifically, Ni(OH)2, NiO, NiOOH, NiCO3·2Ni(OH)2·4H2O, NiC2O2·2H2O, Ni(NO3)2·6H2O, NiSO4, NiSO4·6H2O, fatty acid nickel salt, nickel halide, or a combination thereof, but is not limited thereto.

[0026] The cobalt-containing raw material may be a cobalt-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, or oxyhydroxide, etc., specifically, Co(OH)2, CoOOH, Co(OCOCH3)2·4H2O, Co(NO3)2·6H2O, Co(SO4)2·7H2O, or a combination thereof, but is not limited thereto.

[0027] The manganese-containing raw material may be, for example, manganese-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, oxyhydroxide, or a combination thereof, specifically, manganese oxide such as Mn2O3, MnO2, Mn3O4, etc., manganese salt such as MnCO3, Mn(NO3)2, MnSO4, manganese acetate, manganese dicarboxylate, manganese citrate, fatty acid manganese salt, manganese oxyhydroxide, manganese chloride, or a combination thereof, but is not limited thereto.

[0028] The metal solution may be prepared by adding a nickel-containing raw material, a cobalt-containing raw material, and a manganese-containing raw material to a solvent, specifically, water or a mixed solvent of an organic solvent (e.g., alcohol, etc.) that can be uniformly mixed with water, or may be prepared by mixing an aqueous solution of a nickel-containing raw material, an aqueous solution of a cobalt-containing raw material, and an aqueous solution of a manganese-containing raw material.

[0029] The ammonium cation-containing complexing agent may be, for example, but is not limited to, NH4OH, (NH4)2SO4, NH4NO3, NH4Cl, CH3COONH4, NH4CO3, or a combination thereof. Meanwhile, the ammonium cation-containing complexing agent may be used in the form of an aqueous solution, and in this case, the solvent may be water or a mixture of water and an organic solvent (specifically, alcohol, etc.) that can be uniformly mixed with water.

[0030] The basic compound may be a hydroxide of an alkali metal or an alkaline earth metal, such as NaOH, KOH, or Ca(OH), a hydrate thereof, or a combination thereof. The basic compound may also be used in the form of an aqueous solution, and in this case, the solvent may be water or a mixture of water and an organic solvent (specifically, an alcohol, etc.) that is uniformly miscible with water.

[0031] The basic compound is added to adjust the pH of the reaction solution, and may be added in an amount such that the pH of the metal solution becomes 10.5 to 13, preferably 11 to 13.

[0032] Alternatively, the co-precipitation reaction may be carried out under an inert atmosphere such as nitrogen or argon at a temperature of 40 to 70°C.

[0033] Through the above process, nickel-manganese-cobalt hydroxide particles are produced and precipitated in the reaction solution. The precipitated nickel-manganese-cobalt hydroxide particles can be separated and dried by a conventional method to obtain a transition metal precursor.

[0034] Meanwhile, the content of the lithium source material and the nickel-manganese-cobalt precursor in the reaction mixture may be appropriately adjusted in consideration of the composition of the cathode active material to be finally obtained. For example, the lithium source material and the nickel-manganese-cobalt precursor may be included in the reaction mixture such that the atomic ratio of lithium:transition metal is 1:1.01 to 1.09. Here, the atomic ratio of transition metal means the total number of transition metal atoms, which is the sum of the numbers of nickel, cobalt, and manganese atoms.

[0035] Meanwhile, the reaction mixture may further include a doping source material for improving the stability and properties of the positive electrode active material in addition to the lithium source material and the nickel-manganese-cobalt precursor. As the doping source material, an oxide, hydroxide, sulfide, oxyhydroxide, halide, or a mixture thereof containing one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, In, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo may be used.

[0036] The reaction mixture containing the above-mentioned components may be prepared by adding each component to a mixer or the like and mixing them in a solid phase, but is not limited thereto.

[0037] After the reaction mixture is charged into the first crucible, a primary heat treatment is carried out at a temperature of 500°C to 800°C, preferably 550°C to 700°C.

[0038] When the first heat treatment is performed within the above temperature range, the lithium source material reacts with the nickel-manganese-cobalt precursor to form a pre-calcination mixture in which lithium nickel cobalt manganese oxide having a spinel structure and lithium nickel cobalt manganese oxide seeds having a layered structure are mixed. The following reaction formula 1 illustrates the reaction that occurs during the first heat treatment when LiOH is used as the lithium source material and nickel manganese cobalt hydroxide is used as the nickel-manganese-cobalt precursor. [Reaction Scheme 1] LiOH+[Ni a Mn b Co c ](OH)2→Li[Ni a Mn b Co c ]2O4, Li[Ni a Mn b Co c ]O2

[0039] Meanwhile, the calcination mixture is formed by reacting a low-density lithium source material with the nickel-manganese-cobalt precursor while melting, and therefore has a reduced volume compared to the reaction mixture.

[0040] Specifically, the volume of the calcination mixture formed by the first heat treatment in the above temperature range is 20% to 50%, for example, 20% to 40%, of the volume of the reaction mixture put into the first crucible. If the first heat treatment temperature is less than 500°C, the structure of the nickel-manganese-cobalt precursor, which is the raw material, is hardly changed even after the first heat treatment, and the calcination mixture is formed in a form in which lithium is unevenly attached to the surface, so the effect of volume reduction is negligible. Therefore, if the first heat treatment temperature is less than 500°C, the effect of improving productivity is reduced, and the quality uniformity of the finally produced positive electrode active material is also reduced. On the other hand, if the first heat treatment temperature exceeds 800°C, there is a disadvantage that crystal growth occurs rapidly during the first heat treatment, making it difficult to control the crystal growth and the properties of the final positive electrode material.

[0041] Meanwhile, the first heat treatment may be performed for 1 hour or more, preferably 3 hours or more, and more preferably 3 to 12 hours. When the first heat treatment time is 1 hour or more, moisture and gas generated during the heat treatment can be sufficiently removed, and it is easy to control crystal growth in the second heat treatment.

[0042] Also, the first heat treatment may be performed in an oxygen atmosphere or an air atmosphere. As described above, when sintering is performed at the first heat treatment temperature, a lithium nickel cobalt manganese oxide having a spinel structure is formed. This spinel structure is formed through an oxidation process as described in Reaction Scheme 1. Therefore, under conditions of high oxygen partial pressure, the crystal size increases and the cation mixing value decreases. Therefore, the first heat treatment is preferably performed in an oxygen atmosphere or an air atmosphere having a high oxygen partial pressure.

[0043] Meanwhile, the first crucible may be a crucible commonly used in the art, such as a stainless steel crucible, a nickel crucible, an alloy crucible (e.g., Inconel (registered trademark), Hastelloy (registered trademark), etc.), or an aluminum crucible. Among these, it is preferable to use a stainless steel crucible, a nickel crucible, or an alloy crucible from an economical point of view. An aluminum crucible is easily damaged by a lithium raw material and is therefore difficult to use for a long period of time. In contrast, a stainless steel crucible, a nickel crucible, or an alloy crucible has the advantage of being more durable than an aluminum crucible, but is not suitable for high-temperature firing exceeding 800°C. Therefore, in the past, an aluminum crucible was mainly used in the manufacture of a lithium nickel manganese cobalt-based positive electrode active material. However, since the heat treatment temperature of the first heat treatment is 800°C or less, a stainless steel crucible, a nickel crucible, or an alloy crucible may be used, thereby reducing the cost of replacing the crucible.

[0044] (2) Crushing or classification stage When the calcined mixture is formed through the first heat treatment, the calcined mixture is taken out of the first crucible and crushed or classified.

[0045] The grinding or classification may be carried out by a common grinding or classification method known in the art, such as a ball mill, a jet mill, or a sieving method.

[0046] The crushing or classification step increases the tap density of the calcination mixture and effectively removes impurities such as moisture and carbon dioxide, thereby reducing the volume of the calcination mixture and allowing a larger amount of the calcination mixture to be placed in the second crucible, thereby improving productivity.

[0047] In addition, the calcination mixture is homogeneously mixed during the pulverization or classification process, so that the quality uniformity of the positive electrode active material can be further improved.

[0048] (3) Lithium nickel manganese cobalt-based positive electrode active material formation stage After the crushing or classification process is completed, the crushed or classified pre-calcined mixture is put into a second crucible and subjected to a second heat treatment at a temperature of 700° C. to 1000° C., preferably 750° C. to 1000° C., in an atmosphere with an oxygen partial pressure of 20% or less, to form a lithium nickel manganese cobalt-based positive electrode active material.

[0049] When the second heat treatment is performed at such a high temperature, the lithium nickel manganese cobalt oxide having a spinel structure in the calcination mixture is converted into a layered structure through the reaction shown in Reaction Scheme 2 below, and the lithium nickel manganese cobalt oxide seed having the layered structure undergoes crystal growth. [Reaction Scheme 2] Li[Ni a Mn b Co c ]2O4+ 1 / 2Li2O → Li[Ni a Mn b Co c ]O2

[0050] As shown in Reaction Scheme 2, the process of forming the layered lithium nickel manganese cobalt oxide is a reduction process, so it is advantageous for the formation of the structure to be performed under conditions of low oxygen partial pressure. Specifically, when the second heat treatment is performed under low oxygen partial pressure, the crystal size increases and cation mixing decreases. Therefore, in the present invention, the second heat treatment for forming the layered structure is performed under conditions of an oxygen partial pressure of 20% or less, thereby making it possible to manufacture a positive electrode active material with excellent physical properties and electrochemical characteristics. Specifically, the second heat treatment may be performed in a nitrogen atmosphere, a vacuum atmosphere, a non-flowing atmosphere, or the like.

[0051] In general, gas such as CO2 is generated during the calcination process of lithium raw material and nickel-manganese-cobalt precursor. If unnecessary gas such as CO2 gas is generated, the oxygen partial pressure in the calcination atmosphere decreases, which causes a problem that the physical properties of the formed positive electrode active material are deteriorated. Therefore, in the past, calcination was generally performed in an oxygen atmosphere to produce a high-quality positive electrode active material. However, in the present invention, since CO2 gas is already generated in the first heat treatment, no by-product such as CO2 is generated during the second heat treatment. Therefore, even if calcination is performed in an atmosphere with a low oxygen partial pressure as the second heat treatment, a high-quality positive electrode active material can be produced.

[0052] Meanwhile, the second heat treatment may be performed for 2 hours or more, preferably 4 hours or more, and more preferably 4 to 20 hours. If the second heat treatment is performed for less than 2 hours, crystal growth may not occur sufficiently, which may result in poor high-temperature life and storage characteristics when applied to a battery.

[0053] On the one hand, the content of the calcined mixture fed into the second crucible may be 2 to 10 times, preferably 2 to 6 times, the content of the calcined mixture formed from the first crucible. As described above, since the calcined mixture has a volume reduced by the primary heat treatment compared to the reaction mixture, a larger amount of the calcined mixture can be fed into the second crucible compared to directly feeding the reaction mixture. By maximizing the content of the calcined mixture fed into the second crucible in this way, a larger amount of the positive electrode active material can be obtained from a crucible of the same volume compared to the prior art.

[0054] On the other hand, since the secondary heat treatment is performed at a high temperature, the second crucible is preferably a crucible made of aluminum.

[0055] In addition, in the manufacturing method of the present invention, although not essential, in order to improve the stability and physical properties of the positive electrode active material, a doping raw material substance may be further added to the second crucible before the secondary heat treatment as necessary. Such doping raw material substances may include oxides, hydroxides, sulfides, oxyhydroxides, halides or mixtures thereof containing one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, In, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo.

[0056] The lithium nickel manganese cobalt-based positive electrode active material manufactured by the manufacturing method of the present invention as described above may be represented by the following Chemical Formula 1. [Chemical Formula 1] Li 1+x [Ni a Mn b Co c M 1 1-a-b-c 1-x O2 In Chemical Formula 1, -0.2 ≦ x ≦ 0.2, 0 < a < 1, 0 < b < 1, 0 < c < 1, and the M 1 ​is one or more selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, In, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo.

[0057] The a, b, and c represent the atomic fractions of Ni, Mn, and Co, respectively, and are not limited thereto, but may be, for example, 0.01≦a≦0.98, 0.01≦b≦0.98, 0.01≦c≦0.98, specifically, 0.5≦a≦0.98, 0.01≦b≦0.49, 0.01≦c≦0.49, and more specifically, 0.6≦a≦0.98, 0.01≦b≦0.39, 0.01≦c≦0.39.

[0058] In the manufacturing method of the present invention, firing is performed in an atmosphere with a relatively high oxygen content during the first heat treatment performed at a low temperature to form a spinel structure, and firing is performed in an atmosphere with a relatively low oxygen content during the second heat treatment performed at a high temperature to form a layered structure, thereby making it possible to manufacture a positive electrode active material with large crystal size and little cation mixing.

[0059] In addition, since the manufacturing method of the present invention forms a pre-sintered mixture having a reduced volume compared to the reaction mixture by performing the first heat treatment, a relatively large amount of the pre-sintered mixture can be placed in a crucible for the second heat treatment, resulting in excellent productivity.

[0060] In addition, reaction by-products such as moisture and CO2 are generated during the first heat treatment, and the pre-sintering mixture from which these by-products are removed is used for the second heat treatment. This minimizes deterioration of the sintering atmosphere and the properties of the positive active material caused by the reaction by-products, thereby producing a positive active material of excellent and uniform quality.

[0061] [Example] The present invention will be described in more detail below with reference to specific examples.

[0062] Example 1 LiOH and Ni 0.8 Co 0.1 Mn 0.1(OH)2 was mixed in a mixer in a weight ratio of 1.01:1 to form a reaction mixture, and then 7500g (volume: 8000ml) of the reaction mixture was placed in a stainless steel crucible and subjected to a primary heat treatment at 600℃ for 5 hours in an oxygen atmosphere to form a pre-sintered mixture, which was then frozen. The volume of the pre-sintered mixture was 2000ml, and the weight of the pre-sintered mixture was about 5000g.

[0063] The pre-sintered mixture (10,000 g, volume: 8,000 ml) was crushed and sieved, and then the crushed pre-sintered mixture was placed in an aluminum crucible and subjected to a secondary heat treatment at 800° C. in a nitrogen atmosphere for 10 hours to prepare a positive electrode active material.

[0064] Example 2 Li2CO3 and Ni 0.6 Co 0.2 Mn 0.2 (OH)2 was mixed in a mixer in a weight ratio of 1.07:1 to form a reaction mixture, and 7500g (volume: 8000ml) of the reaction mixture was placed in a stainless steel crucible and subjected to a primary heat treatment at 750℃ in an oxygen atmosphere for 5 hours to form a pre-sintered mixture, which was then frozen. The volume of the pre-sintered mixture was 2000ml, and the weight of the pre-sintered mixture was about 5000g.

[0065] The pre-sintered mixture (10,000 g, volume: 8,000 ml) was crushed and sieved, and then the crushed pre-sintered mixture was placed in an aluminum crucible and subjected to a secondary heat treatment at 830° C. in a nitrogen atmosphere for 13 hours to prepare a positive electrode active material.

[0066] Comparative Example 1 A positive electrode active material was prepared in the same manner as in Example 1, except that the second heat treatment was performed in an oxygen atmosphere.

[0067] Comparative Example 2 A positive electrode active material was prepared in the same manner as in Example 2, except that the second heat treatment was performed in an oxygen atmosphere.

[0068] Comparative Example 3 A positive electrode active material was prepared in the same manner as in Example 1, except that the primary heat treatment temperature was 300°C. The volume of the pre-sintered mixture prepared after the primary heat treatment was 7500 ml, and there was almost no volume reduction. The weight of the pre-sintered mixture was measured to be about 6700 g. The weight reduction rate of the pre-sintered mixture in Comparative Example 3 was smaller than that in Examples 1 and 2, which is believed to be due to the low moisture and gas removal rate caused by the low primary heat treatment temperature.

[0069] Comparative Example 4 Li2CO3 and Ni 0.6 Co 0.2 Mn 0.2 (OH)2 was mixed in a mixer in a weight ratio of 1.07:1 to form a reaction mixture, and 7500 g (volume: 8000 ml) of the reaction mixture was placed in an aluminum crucible and subjected to a primary heat treatment at 750°C in an oxygen atmosphere for 5 hours to form a pre-sintered mixture, which was then frozen.

[0070] Thereafter, the pre-calcined mixture was removed from the aluminum crucible, and without being crushed or sieved, it was subjected to a second heat treatment in the same crucible at 830° C. in a nitrogen atmosphere for 13 hours to prepare a positive electrode active material.

[0071] Experimental Example 1: Measurement of crystal size and cation mixing of positive electrode active material The crystal size and cation mixing value of the positive active materials prepared in Examples 1 and 2 and Comparative Examples 1, 2, and 4 were measured by XRD (X-ray diffraction) refinement analysis, and the measurement results are shown in Table 1 below.

[0072] [Table 1]

[0073] As shown in Table 1, the positive electrode active materials of Examples 1 and 2, in which the first heat treatment was performed in an oxygen atmosphere and the second heat treatment was performed in a nitrogen atmosphere, exhibited larger crystal sizes and lower cation mixing ratios than the positive electrode active materials of Comparative Examples 1 and 2, in which the first and second heat treatments were both performed in oxygen atmospheres. On the other hand, it can be seen that the positive electrode active material of Comparative Example 4 exhibited a similar crystal size to that of Example 2, but a higher cation mixing ratio.

[0074] Experimental example 2: Evaluation of life characteristics and resistance increase rate The positive electrode active materials prepared in Examples 1 and 2 and Comparative Examples 1, 2, and 4, PVdF (polyvinylidene fluoride) binder, and carbon black were dispersed in an NMP (N-methylpyrrolidone) solution in a weight ratio of 97.5:1.5:1.0 to prepare a slurry, which was then applied to an Al current collector and rolled using a roll press to prepare a positive electrode.

[0075] In addition, a negative electrode active material, natural graphite, a carbon black conductive material, and a PVdF (polyvinylidene fluoride) binder were mixed in a weight ratio of 95.6:1.0:3.4 in an N-methylpyrrolidone solvent to prepare a composition for forming a negative electrode, which was then applied to a copper current collector to prepare a negative electrode.

[0076] An electrode assembly was prepared by interposing a porous polyethylene separator between the positive and negative electrodes prepared as described above, and the electrode assembly was placed inside a case, and an electrolyte was injected into the case to prepare a coin cell lithium secondary battery. The electrolyte was prepared by dissolving lithium hexafluorophosphate (LiPF6) at a concentration of 0.7M in an organic solvent consisting of ethylene carbonate / ethyl methyl carbonate (EC:EMC mixed volume ratio=3:7).

[0077] The coin cell manufactured as described above was charged and discharged twice at room temperature under the conditions of a charge cut-off voltage of 4.25V, a discharge cut-off voltage of 2.5V, and 0.1C / 0.1C, and the initial charge / discharge capacity and initial resistance were measured. Then, the coin cell was charged and discharged at 45°C under the conditions of a charge cut-off voltage of 4.25V, a discharge cut-off voltage of 2.5V, and 0.3C / 0.3C, and the capacity retention rate (Capacity Retention [%]) and DC resistance increase rate (DCR Incress [%]) after 50 cycles were measured. The measurement results are shown in Table 2.

[0078] [Table 2]

[0079] From Table 2, it can be seen that the batteries using the positive electrode active materials of Examples 1 and 2 have superior capacity characteristics and cycle characteristics compared to the batteries using the positive electrode active materials of Comparative Examples 1, 2 and 4.

Claims

1. A reaction mixture including a lithium source material and a nickel-manganese-cobalt precursor is put into a first crucible and subjected to a first heat treatment at a temperature of 500° C. to 800° C. in an oxygen atmosphere to form a pre-calcination mixture; removing the calcined mixture from the first crucible and pulverizing or classifying the calcined mixture; and feeding the ground or classified pre-calcined mixture into a second crucible and subjecting it to a second heat treatment at a temperature of 700° C. to 1000° C. in an atmosphere having an oxygen partial pressure of 20% or less or in a vacuum atmosphere to form a lithium nickel manganese cobalt-based positive electrode active material. a volume of the calcination mixture formed after the first heat treatment is 20% to 50% of a volume of the reaction mixture introduced into the first crucible; The content of the calcination mixture introduced into the second crucible is 2 to 10 times the content of the calcination mixture formed from the first crucible; The lithium nickel manganese cobalt-based positive electrode active material is represented by the following chemical formula 1: [Chemical formula 1] Li 1+x [Ni a Mn b Co c M 1 1-a-b-c ] 1-x O 2 In the formula 1, -0.2≦x≦0.2, 0.6≦a≦0.98, 0.01≦b≦0.39, and 0.01≦c≦0.39; Said M 1 is one or more selected from the group consisting of Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo.

2. The method of claim 1 , wherein the second heat treatment is performed in a nitrogen atmosphere.

3. The method for producing a positive electrode active material according to claim 1 or 2, wherein the lithium source material is at least one selected from the group consisting of lithium hydroxide and lithium carbonate.

4. 4. The method for producing a positive electrode active material according to claim 1, wherein the nickel-manganese-cobalt precursor is at least one selected from the group consisting of nickel manganese cobalt hydroxide, nickel manganese cobalt oxyhydroxide, nickel manganese cobalt carbonate, and nickel manganese cobalt organic complex.

5. The method for producing a positive electrode active material according to claim 1 , wherein the reaction mixture further comprises a doping source material.

6. 6. The method for producing a positive electrode active material according to claim 5, wherein the doping source material is an oxide, a hydroxide, a sulfide, an oxyhydroxide, a halide, or a mixture thereof, containing one or more elements selected from the group consisting of Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo.

7. 7. The method for producing a positive electrode active material according to claim 1, wherein the first crucible is a stainless steel crucible, a nickel crucible, an Inconel (registered trademark) crucible, or a Hastelloy (registered trademark) crucible.

8. The method for producing a positive electrode active material according to claim 1 , wherein the first heat treatment is performed for one hour or more.

9. The method of claim 1 , further comprising adding a doping source material to the second crucible before the second heat treatment.

10. The method for producing a positive electrode active material according to claim 1 , wherein the second heat treatment is performed for 2 hours or more.

Citation Information

Patent Citations

  • Manufacture of linio2 for lithium secondary battery

    JP1997259881A

  • Lithium secondary battery positive electrode active substance, its manufacturing method, and lithium secondary battery

    JP2005251756A

  • Manufacturing method of lithium / transition metal composite oxide

    JP2007214118A

  • Nickel-containing hydroxide, nickel-containing oxide, lithium-mixed nickel oxide and methods for manufacturing them

    JP2010070431A

  • Positive electrode active material for nonaqueous electrolyte secondary battery, method of manufacturing the same, and nonaqueous electrolyte secondary battery

    JP2010211925A